Juridical Review of Debtor Data Dissemination in Online Loan Default Cases - Santyaningtyas, Ayu Citra; Warah Atikahv; Tri Handy Primadi (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
In general, in online loans, when a default occurs, the creditor will contact all of the debtor's contacts via telephone, SMS, or via the Whatsapp application by spreading the debtor's data. This may be valid if it refers to the legal terms of an agreement as set forth in POJK number 77/POJK.01/2016 because the debtor is considered to have violated the agreement or contract. However, Law Number 11 of 2008 concerning Information and Electronic Transactions (abbreviated as the ITE Law) prohibits anyone who intentionally and without rights distributes electronic information and/or documents containing threats of violence or intimidation. This is in accordance with the mandate of Article 28G paragraph (1) of the Constitution of the Republic of Indonesia which states that: "everyone has the right to personal, family, honor, dignity and property protection under his authority and has the right to feel safe and is entitled to protection from the threat of fear to do or not do something.